ZnxCd1-xS nanoparticles dispersed on CoAl-layered double hydroxide in 2D heterostructure for enhanced photocatalytic hydrogen evolution - Li, Hongying; Hao, Xuqiang; Liu, Yang; Li, Yanbing; Jin, Zhiliang (Journal of colloid and interface science, 2020)
CoAl-LDH has a larger specific surface area than ZCS nanoparticles, which makes ZCS evenly dispersed and inhibits its aggregation. The uniform dispersion of the ZCS nanoparticles exposes more active sites and facilitates the catalyst reaction. In addition, the 2D heterostructure formed by ZCS and CoAl-LDH is beneficial to the increase of hydrogen production. [Display omitted] CoAl-LDH and ZnxCd1-xS (ZCS) were successfully assembled. By studying the microstructure of the catalysts, it was found that the agglomerated ZCS nanoparticles were equably dispersed on the hexagonal plate-like CoAl-LDH surface. The increase of the specific surface area of the composite catalyst further proves that the agglomeration state of ZCS nanoparticles has been improved. When the mass of the introduced CoAl-LDH is 20% of the ZCS, the maximum hydrogen production after the optimization is 1516 μmol/5h, which is about 6.9 times that of pure ZCS. UV–vis DRS in the range of 250–800 nm proved that the visible light absorption intensity of the composite is enhanced compared to pure materials. Electrochemical and photoluminescence experiments proved that the heterostructure formed between ZCS and CoAl-LDH accelerates photoelectron transfer and inhibits the recombination of electrons and holes. In addition, possible mechanisms of the sample were explored by UV–vis DRS and Mott-Schottcky.